'Scènes de Gynécées, ' figured Ostraca from New Kingdom Egypt iconography and intent - Backhouse Joanne (Archaeopress Egyptology, 2020)
This work examines images of women and children drawn on ostraca from Deir el-Medina, referred to in previous scholarship as 'Scènes de Gynécées'. This publication represents the first systematic study of this material, and it brings together ostraca from museums worldwide to form a corpus united contextually, thematically and stylistically.